Fundamentos jurisprudenciales de la política penal de irán relacionados con la propagación de la prostitución del código penal de 2013 - Ardavan Arzhang; Abozar Abozar Fadakar Davarani; Mohammad Nozari Ferdowsieh (Ius Humani. Jornal do direito, 2018)
The legislator has acted to criminalize the field of public chastity in order to preserve public morality; one of these cases considers prostitution. Publication of some news and images, especially those that may appear today in various mass media, such as Internet websites, certainly leads to the dissemination and spread of content that contradicts public morality and ethics, that confronts ethical norms and values. That’s why the publication of such information is prohibited by law. Concerning the spread of prostitution, this paper analyzes two instances of abuse, that contradict public morality and are related to each other. The main question in this paper is, what does the Iranian criminal policy do against the spread of prostitution, covered in the Islamic Penal Code approved in 2013? After an introduction (Chapter I), we analyze some jurisprudential concepts and principles related with this matter (Chapter II). In Chapter III we see some examples of the spread of prostitution in domestic law. Finally, we take care of the role of corruption in the spread of prostitution (Chapter IV) and then we resume some conclusions (Chapter V).